SEROLOGICAL CHANGES AGAINST HEPATITIS B SURFACE ANTIGEN IN CHILDREN AND ADOLESCENTS RECEIVING CHEMOTHERAPY FOR ACUTE LEUKEMIA - Seung Beom Han; Hye Jo Shin; Eui Soo Lee; Jae Wook Lee; Nack-Gyun Chung; Bin Cho; Jin Han Kang (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Vaccination for hepatitis B virus (HBV) after chemotherapy among pediatric patients with acute leukemia is still a debated issue. We investigated HBV immunity before and after chemotherapy and assessed immune response to re-vaccination after chemotherapy.